Systematic Analysis of E3 Ligase-Related Genes Identified UBE2L3 as a Prognostic Biomarker Associated With Drug Resistance in Acute Myeloid Leukemia - Ling C; Cao N; Wang H; Wan Y; Liang X; Guo J; Xiao M; Zhang Q; Zhai Z (International Journal of General Medicine)
Chun Ling,1,2 Nengneng Cao,1 Huiping Wang,1 Yang Wan,1 Xue Liang,1 Jinjing Guo,1 Meng Xiao,1 Qiguo Zhang,2 Zhimin Zhai1 1Department of Hematology, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230000, People’s Republic of China; 2Department of Hematology, Affiliated Chuzhou Hospital of Anhui Medical University, First People’s Hospital of Chuzhou, Chuzhou, Anhui, 239001, People’s Republic of ChinaCorrespondence: Zhimin Zhai, Department of Hematology, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230000, People’s Republic of China, Email zzzm886@163.comBackground: Acute Myeloid Leukemia (AML) is a prevalent neoplastic disorder. The roles of E3 ubiquitin ligases and related genes in AML drug resistance and prognosis remain unclear.Methods: Genes were identified from GeneCards and UniProt databases, differentially expressed genes were selected based on transcriptional sequencing data from wild-type and Adriamycin-resistant HL60 (HL60/WT & HL60/ADR) cell lines, and the intersection of these three sources was taken. We then constructed a prognostic model comprising five genes (HBP1, RNF130, RMND5B, TRIM32, and UBE2L3) through univariate Cox and LASSO regression analyses in the TCGA cohort and validated it in the BeatAML2.0 cohort. Finally, the expression of UBE2L3 was verified in cell lines and clinical case specimens.Results: The model accurately predicted AML prognosis and identified the UBE2L3 gene within the model as a high-risk biomarker associated with drug resistance, significantly influencing AML outcomes.Conclusion: The high expression of UBE2L3 is a reliable biomarker for drug resistance and poor prognosis of acute myeloid leukemia.Keywords: E3 ubiquitin ligase, prognostic model, UBE2L3, acute myeloid leukemia, drug resistance